Impact of clear aligner therapy on tooth pain and masticatory muscle soreness. (5th October 2020) - Tran, Johnny; Lou, Tiantong; Nebiolo, Bianca; Castroflorio, Tommaso; Tassi, Ali; Cioffi, Iacopo
Abstract: Background: Clinical findings suggest that orthodontic treatment with clear aligners (clear aligner therapy/CAT) may cause masticatory muscle soreness in some patients. Objective: This multi‐site prospective study investigated tooth pain and masticatory muscle soreness and tenderness in patients undergoing CAT and explored whether psychological traits affected these outcomes. Methods: Twenty‐seven adults (22F, 5M; mean age ± SD=35.3 ± 17.6 years) about to start CAT were recruited at three clinics. During CAT, they reported on 100‐mm visual analogue scales their tooth pain, masticatory muscle soreness and stress three times per day over 4 weeks (week 1 =  baseline ; week 2 =  dummy aligner ; week 3 =  first active aligner ; week 4 =  second active aligner ). Pressure pain thresholds (PPTs) were measured at the masseter and temporalis at baseline and after week 4. Mixed models were used to evaluate the outcome measures over time. Results: Clear aligner therapy caused mild tooth pain, which was greater with the passive than the first and second active aligners (both P  < .001). Mild and clinically not relevant masticatory muscle soreness was produced by all aligners (all P  < .05), with the first active aligner producing less soreness than the dummy aligner ( P  < .001). PPTs did not change significantly after 4 weeks. Both tooth pain and masticatory muscle soreness were affected by stress and trait anxiety, whilst muscle soreness was affected also by oral behaviours. Conclusions: In the short term, CAT produces tooth pain and masticatory muscle soreness of limited significance. Frequent oral behaviours are related to increased masticatory muscle soreness during CAT. The medium‐ and long‐term effects of CAT should be further explored.